Is Umbilical Cord Blood Therapy an Effective Treatment for Early Lung Injury in Growth Restriction? - Allison, Beth J.; Youn, Hannah; Malhotra, Atul; McDonald, Courtney A.; Castillo-Melendez, Margie; Pham, Yen; Sutherland, Amy E.; Jenkin, Graham; Polglase, Graeme R.; Miller, Suzanne L. (Frontiers in Endocrinology, 2020)
Fetal growth restriction (FGR) and prematurity are often co-morbidities, and both are risk factors for lung disease. Despite advances in early delivery combined with supportive ventilation, rates of ventilation-induced lung injury (VILI) remain high. There are currently no protective treatments or interventions available that target lung morbidities associated with FGR preterm infants. Stem cell therapy, such as umbilical cord blood (UCB) cell administration, demonstrates an ability to attenuate inflammation and injury associated with VILI in preterm appropriately grown animals. However, no studies have looked at the effects of stem cell therapy in growth restricted newborns. We aimed to determine if UCB treatment could attenuate acute inflammation in the first 24 h of ventilation, comparing effects in lambs born preterm following FGR with those born preterm but appropriately grown (AG). Placental insufficiency (FGR) was induced by single umbilical artery ligation in twin-bearing ewes at 88 days gestation, with twins used as control (appropriately grown, AG). Lambs were delivered preterm at ~126 days gestation (term is 150 days) and randomized to either immediate euthanasia (unventilated controls, AGUVC and FGRUVC) or commenced on 24 h of gentle supportive ventilation (AGV and FGRV) with additional cohorts receiving UCB treatment at 1 h (AGCELLS, FGRCELLS). Lungs were collected at post-mortem for histological and biochemical examination. Ventilation caused lung injury in AG lambs, as indicated by decreased septal crests and elastin density, as well as increased inflammation. Lung injury in AG lambs was attenuated with UCB therapy. Ventilated FGR lambs also sustained lung injury, albeit with different indices compared to AG lambs; in FGR, ventilation reduced septal crest density, reduced alpha smooth muscle actin density and reduced cell proliferation. UCB treatment in ventilated FGR lambs further decreased septal crest density and increased collagen deposition, however, it increased angiogenesis as evidenced by increased vascular endothelial growth factor (VEGF) expression and vessel density. This is the first time that a cell therapy has been investigated in the lungs of growth restricted animals. We show that the uterine environment can alter the response to both secondary stress (ventilation) and therapy (UCB). This study highlights the need for further research on the potential impact of novel therapies on a growth restricted offspring.